Evaluation of ciguatoxins in seafood and the environment in Europe. Issue 5 (19th May 2021) - Diogène, Jorge; Rambla, Maria; Campàs, Mònica; Fernández, Margarita; Andree, Karl; Tudó, Angels; Rey, Maria; Sagristà, Nuria; Aguayo, Paloma; Leonardo, Sandra; Castan, Vanessa; Costa, Jose Luis; et al.
Abstract : The present document corresponds to Deliverable No. 10: "Final report (1st of April 2016‐31stOctober2020)." of the specific agreement "EVALUATION OF CTXs IN SEAFOOD AND THE ENVIRONMENT for the RISK ASSESSMENT OF CIGUATERA FISH POISONING (CFP), with the consequent OBTENTION OF REFERENCE MATERIAL" within the Framework Partnership Agreement GP/EFSA/AFSCO/2015/03 "Risk characterization of ciguatera food poisoning in Europe"© Institute for Research and Technology in Food and Agriculture (IRTA), Universidad de Las Palmas de Gran Canarias (ULPGC), Canary Health Service (ServicioCanario de la Salud, SCS), Instituto Português do Mar e da Atmosfera I.P (IPMA), State General Laboratory (SGL) / Ministry of Health, Aristotle University of Thessaloniki (AUT), 2021